Quadruple Helix Model on Leadership Succession in Improving Bank BNI Company Performance (Based on Total Quality Management) - KO Pangaribuan, Nova; Djamil, Masyhudzulhak (Dinasti International Journal of Management Science, 2024)
This research aims to obtain strategies or policies through the Quadruple Helix Model on leadership succession to improve Bank BNI company performance. Mixed research method with a population of 5 regional units at BNI with a pairwise comparisons questionnaire used to collect data based on indicators from research variables using the AHP (Analytical Hierarchy Process) data analysis technique which is a decision support model (Thomas L. Saaty). The first criterion (criteria-1) in this research is: Planning, Investigation, Coordination, Evaluation, Supervision, Staffing, Negotiation, Representation. The second variable or criterion (criteria-2) in Succession and Leadership used is: Candidate Recruitment, Candidate Selection, Customer Focus, Obsession with Quality, Continuous System Improvement, Education and Training. In the final section there are alternatives that can be used to improve bank company performance using the QH model, namely: Organizational Strategy, Business Strategy, Intellectual Strategy and Customer Strategy. From model testing, results were obtained that met the consistency criteria and also proved its sensitivity and stability. The Quadruple Helix model in this research produces Organizational Strategy as a priority and good candidate selection can play a role in the success of Leadership Succession which has a focus on customers in improving Bank Company Performance.